Clarification of the Magnetocapacitance Mechanism for Fe3O4-PDMS Nanocomposites. (24th March 2015) - Guobin, Chen; Hui, Yang; Xiaoming, Zhang; Jun, Liu; Jun, Tang
Abstract : We mainly focused on the magnetocapacitance effect of Fe3 O4 -PDMS nanocomposites. We also proposed the preparation method and measured microstructures, magnetic properties, and magnetocapacitance value of the nanocomposites. The magnetocapacitance measurement results show that the nanocomposites have magnetocapacitance property, the magnetocapacitance with magnetic field depends on the magnetic property, and the value at the same magnetic field is increasing with the volume fraction of Fe3 O4 nanoparticles. The magnetocapacitance model is proposed to explain this phenomenon by analyzing the magnetic interaction between particles and the viscoelasticity of PDMS. We also calculated the theoretical capacitance value of all samples using the magnetization of nanoparticles and mechanical parameters of PDMS. From the theoretical values, it is concluded that the model we proposed can well explain the magnetocapacitance effect of Fe3 O4 -PDMS nanocomposites.